Are individual stock returns predictable? - Zeng H; Marshall BR; Nguyen NH; Visaltanachoti N (SAGE Publications on behalf of the University of New South Wales, 2022)
We show that the previously documented predictability of macroeconomic and technical variables for market returns is also evident in individual stock returns. Technical variables generate better predictability on firms with high limits to arbitrage (small, illiquid, volatile firms), while macroeconomic variables better predict firms with low limits to arbitrage. Technical predictors show a stronger predictive power for high limits to arbitrage firms across the business cycle, whereas macroeconomic variables capture more predictive information for firms with low limits to arbitrage during recessions.
Keywords: Business cycle; cross-sectional predictability; firm-level predictability; limits to arbitrage; macroeconomic and technical predictors; principal component analysis